Management of patients with low back pain admitted to hospital: An observational study of usual care. (7th October 2022) - Melman, Alla; Maher, Chris G.; Needs, Chris; Richards, Bethan; Rogan, Eileen; Teng, Min Jiat; Machado, Gustavo C.
Abstract: Background: Knowledge gaps exist around diagnostic and treatment approaches for patients admitted to hospital with low back pain. Methods: Medical record review of patients admitted to three Sydney teaching hospitals with a provisional emergency department diagnosis of non‐serious low back pain, from 2016 to 2020. Data on demographic variables, hospital costs, length of stay (LOS), diagnostic imaging and analgesic administration were extracted. Logistic regression was used to identify predictors of longer hospital stay, advanced imaging, and concomitant use of sedating medicines. Results: Median inpatient LOS for non‐specific low back pain was 4 days (interquartile range [IQR] 2‐7), and for radicular low back pain was 4 days (IQR 3‐10). Older patients with non‐serious low back pain were more likely to stay longer, as were arrivals by ambulance. Plain lumbar radiography was used in 8.3% of admissions, whereas 37.6% of patients received advanced lumbar imaging (computed tomography or magnetic resonance imaging). Opioids were administered in 80% of admissions; 49% of patients with radicular low back pain were given an antiepileptic in addition to an opioid. In all, 18.4% of admissions resulted in at least one hospital‐acquired complication, such as an accidental fall (3.1%) or a medication‐related adverse effect (13.3%). Physiotherapists saw 82.6% of low back pain admissions. Costs of inpatient care were estimated at a mean of AU 14 000 per admission. Conclusions: We noted relatively high rates of concomitant use of sedating pain medicines and referrals for advanced lumbar imaging and laboratory tests. Strategies to address these issues in inpatient care of low back pain are needed.